Implementation of blended learning And its impact on trainees - Arsyil Waritsman (Balai Diklat Keagamaan Ambon, 2022)
This study aims to (1) describe how blended learning is implemented in training activities; and (2) how the impact of the implementation of blended learning. This research uses the systematic literature review method which is focused on several stages, namely planning, reviewing, and documenting. The data used is secondary data in the form of articles related to the implementation of blended learning in training activities published in national journals in the period from 2019 to 2022 in the google scholar and neliti databases. Data is analyzed through several stages, including data collection, data reduction, data presentation, and concluding. The findings show that (1) in the implementation of blended learning, several learning platforms are used to support the implementation of learning in training activities such as zoom, Webex, and google meetings for face-to-face virtually, then also supported by the use of learning management systems (LMS) both moodle-based LMS, Edmodo, google classroom, Schoology and the use of several online media such as youtube, Kahoot and (2) the implementation of blended learning has an impact that positive such as increasing the understanding of trainees both in terms of knowledge and skills, then in terms of affective, trainees become more motivated to learn, interest in learning is increasing and the learning independence of trainees is increasing.